Newspaper coverage of water security issues in the water-stressed Northern Province of Sri Lanka: An explorative study of three Tamil dailies - Rubini, S.; Kumarendran, B.; Raguram, S.; Sriskandarajah, N. (Wiley, 2023)
Newspapers remain as an effective medium for circu- lating information among the public in the North of Sri Lanka and have the potential to influence public opinion and people’s behavior regarding sustainable use of groundwater. This study investigated the extent and scope of newspaper coverage on the subject of water security in the Northern Province of Sri Lanka. Three newspapers, namely, Yarl Thinakkural, Uthayan, and Valampuri were chosen on the basis of readership, circulation in print form, and for being daily local or regional papers in Tamil. The content analysis of 1214 articles published in 2019 and 2020 in the three papers indicated that as much as 80% of space in the papers was allocated to reporting general news items and events in the community related to new water projects, rain and floods or drought events and announcements of allocation of irrigation water for farming. Only 20% of newspaper space was taken up by non-news articles including advertisements related to water. We conclude by saying that the effect of these newspapers on their audiences would merely be to inform rather than to set agendas or frame the discourse in society, let alone persuade readers enough to make changes. The study revealed the significant potential that exists for newspapers to shift their culture of simply reporting of facts in a dispassionate way to one of environmental journalism with a degree of advocacy in view of the critical nature of the security of groundwater in the Northern Province.
Keywords: Media reporting; Newspaper coverage; Northern Province; Sri Lanka; Water security